Analisis Perubahan Desain Karakter dalam GIM SERI DREADOUT Pendekatan Manga Matrix - Rinaldi, Rana Syakirah; Saefudin, Ahmad Thabathaba’i (Jurnal Seni Nasional Cikini, 2023)
Game is an interactive media that can create a space of imagination. DreadOut is a digitale game that adapts Indonesian culture as an entertainment aspect in the game, By bringing Indonesian ghosts. In its development, visual appearance is important in building an interesting game, one of which is the characters. There are differences in kuntilanak and tuyul characters in Dreaout 1 and Dreadout 2. This research dissects the differences between these characters using a manga matrix approach. It is hoped that this research will be a reference as a development of visual creation of characters in the game, in order to develop interesting characters according to the intended target market.